ОРЧИн ҮеИйн УЛС ТөРИйн наМУУдЫн ХөГЖЛИйн ХандЛаГа - С.ЗҮЛЬФИКАР (Politology, 2023)
A political party is a group of people that is organized for the purpose of winning government power by election or other means. Political parties found in the vast majority of counties and in most political system. A variety of classifications have been used for political parties. He most important are the following: elite and cadre political parties; mass political parties; catch all parties etc. By the same time party system is classified as one party system, how party system and multi-party system. Although political parties are defined by a central function (the filling of political office and wielding of government power), their impact on the political system is substantially broader and more complex. In the process of developing collective goals, parties also help to articulate and aggregate the various interests found in society. The fact that national parties invariably articulate the demands of a multitude of groups forces them to aggregate these interests by drawing then together into a coherent whole, balancing competing interests against each other. Final goal for political parties is defined by competing for the government or state power. Parties are the chief means by which political power is exercised in Mongolia.